Agriculture exports performance in Malaysia / Zubir Azhar, Noor Zahirah Mohd Sidek - Azhar, Zubir; Mohd Sidek, Noor Zahirah (Institute of Research Management & Innovation (IRMI), 2010)
This paper examines the impact of exchange rate risk on the agriculture exports in the era of recurring financial crises and global economic instability. Exchange rate risk is captured by misalignments in the real bilateral US-RM exchange rate. This paper is divided into two parts. First, the incidence of exchange rate misalignment is observed using price-based approach (purchasing power parity) and model-based approach (behavioural equilibrium exchange rate). Then, the estimated exchange rate misalignment is used as a variable in the export model to capture the impact of risks. In addition, the estimated misalignments are segregated into events of overvaluation and undervaluation to further comprehend their individual impact. Results suggest that in the long run, overvaluation has a significant negative impact on palm oil exports. The opposite however, could not be construed in the case of undervaluation which suggests asymmetries in the impact of over- and undervaluation of the exchange rate. Other agriculture exports do not exhibit significant long run relationship with exchange rate misalignment. In summary, it is imperative that policy-makers avoid both over- and under-valuation and keep the real exchange rate in line with the economic fundamentals especially in the case of palm oil exports.